Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content 1. Practice of Islamic Education Teachers of Prophetic Methods in Arousing Motivation When Teaching the Holy Quran in the Primary Stage in Jeddah Governorate Mr. Abdulaziz Abdullah Alsahli 2. Evaluating the content of the English book for the third grade secondary in Saudi Arabia in light of the future skills Mrs. Lama Abdullah AL-Tamimi, Dr. Eman Hussain Abu Saleem 3. Analyzing the Content of English Language Textbook for the Sixth Elementary Grade in the Kingdom of Saudi Arabia in Light of Multiple Intelligences Theory Mrs. Amani Abdullah Hamad Alfaisal , Prof. Maha Ibrahim Al-Kaltham 4. Digital Citizenship Dimensions in Arabic Language Curricula for Secondary Stage from View of Its Teachers in Makkah Al Mukarramah: Qualitative and Quantitative Study Mrs. Afnan Omar Masoud , Prof. Hanan Sarhan Al-Nimri 5. The impact of using Virtual laboratory applications inside the classroom on development academic achievement in science among eighth grade students Mr. Omar Hamdan Salim Alhosni 6. The Effectiveness of Using Some Active Learning strategies on the development of grammatical skills of eighth grade female students in the Republic of Yemen Mrs. Haifa Ali Al-Wajih 7. Content Analysis of Digital Skills Course for Primary Stage in the Kingdom of Saudi Arabia in Light of Digital Citizenship Values Mrs. Nouf Majed Saad Alshuhaywin, Prof. Ajlan Mohammed H. Alshehri